(untitled) (Scientific journal of the Fergana State University, 2024)
Nowadays, maintaining bio-diversity is one of the Doric treatments. It is distinguished by the fact that each species in nature has an important Achaemenid. One of the leading families in the flora of Uzbekistan is the cornflower family (Fabaceae), characterized by an abundance of species and species. But in addition to the fact that the family of cornflowers (Fabaceae) is rich in the number of species in our republic, the Red Book also ranks high among the included families. The fact that representatives of the cornflower family (Fabaceae) form protein-rich legumes, and the peculiarity of nitrogen accumulation in the root causes a lot of use of these plants. One of the representatives of the dwarf family (Fabaceae), Astragalus rubellus Goutsch is an endem species for the Fergana Valley. This plant has white fluffy hairs that reach up to 35 cm in height, without stems, perennial, 30-35 cm long, with a thin thick pubescence, leaves are 14-18 pairs of ovoid. It is necessary to dissuade the regions where this plant is encountered from livestock, mainly from anthropogenic influences.